Prevalence of Sexual Victimization Among Female and Male College Students: A Methodological Note With Data. Issue 11 (June 2022) - Jouriles, Ernest N.; Nguyen, Jamie; Krauss, Alison; Stokes, S. Lynne; McDonald, Renee
This study provides insight on how sample recruitment methods may affect reported rates of sexual victimization on college campuses. The study compares sexual victimization rates among students who complete surveys after initial requests with those who complete them only after multiple reminders. Using probability sampling methods, undergraduate students from 12 universities were invited to complete a survey on campus violence; initial invitations were followed with up to five reminders. Women ( n = 1, 008) and men ( n = 344) who completed surveys were categorized as early, middle, or late responders based on the number of reminders required to convert them from non-responders to responders. About 24.2% of women and 15.6% of men reported sexual victimization in the previous two months. In initial analyses, female early and late responders did not differ on sexual victimization, but males did. Male late responders reported higher rates of sexual victimization than early responders. In sensitivity analyses that re-defined early and late responders, women who were early responders reported more sexual victimization than women who were late responders, while men who were early responders reported less sexual victimization than men who were late responders. These findings suggest that researchers may underestimate sexual victimization rates for male college students unless multiple attempts are made to solicit their participation. Researchers are encouraged to utilize multiple reminders to increase research participation.